Organizational and pedagogical conditions for ensuring the quality of professional training of future primary school teachers - Iliichuk, Liubomyra (Scientific notes of the pedagogical department, 2025)
The article emphasizes that the growth of educational risks caused by dynamic changes in the environment, transformations in educational policy, technological and social challenges significantly affect the quality of professional training of future primary school teachers. This necessitates the identification and theoretical justification of a set of organizational and pedagogical conditions capable of ensuring the stability and adaptability of the educational process, as well as their effective integration into the internal quality assurance system of higher education institutions. The purpose of the study is to theoretically substantiate the organizational and pedagogical conditions that ensure the quality of professional training of future primary school teachers, to determine their content and functional purpose in the higher education system. The generalization of theoretical approaches and practical experience has made it possible to interpret organizational and pedagogical conditions as an integrated complex of productive and interrelated factors that ensure the implementation of the educational process in accordance with higher education standards, labor market needs, and stakeholder demands. The following key conditions have been identified: consistency of the goals and content of the educational program with higher education standards; rational organization of the educational process based on student-centeredness, academic integrity, and innovative teaching technologies; resource and infrastructure support for educational activities, covering human, material, technical, educational, methodological, information, and financial resources; effective institutional management of the internal system of higher education quality assurance; orientation of the educational process towards achieving the predicted learning outcomes and the formation of professional competence of future specialists. It is concluded that the identified organizational and pedagogical conditions constitute the strategic basis for improving the quality of professional training of future primary school teachers. Their implementation ensures the consistency of learning objectives, content, and outcomes, enhances the competence potential of learning, contributes to the sustainability of the educational process, and develops an effective internal quality assurance system.